The Impact of AI on Family Communication: A Narrative Review on Children’s Respect for Parents in Developing Southeast Asia - Farisal, Umar (Indonesian Journal Publisher, 2025)
This study examines the impact of Artificial Intelligence (AI) on family communication, parental roles, and children's respect for parents in Southeast Asia. Using a narrative review method, we systematically analyzed peer-reviewed articles published between 2019 and 2024 from databases such as Scopus, Web of Science, and Google Scholar. The findings indicate that AI enhances connectivity within families by facilitating real-time communication and personalized parenting support. However, it also poses challenges, particularly in undermining parental authority and reducing face-to-face interactions. Socioeconomic and cultural factors significantly influence AI adoption, with higher-income families benefiting more from AI-driven parenting tools. The study highlights the need for digital literacy programs and ethical AI policies to mitigate these challenges. Future research should explore long-term effects of AI on family dynamics and develop frameworks that integrate AI with traditional parenting approaches.